LINEAR KINETIC VARIABLES AND THEIR RELATIONSHIP IN THE MOTOR ASSIGNMENT FOR THE ARABIC JUMP SKILL FOR GYMNASTICS STUDENTS - Mohammad Faiz Saheb; Hasanain Ali Kadhim; Qahtan Khudhair Abbas (Galaxy International Interdisciplinary Research Journal, 2023)
The study focused on the importance of the Arabic jump skill in gymnastics for second-stage students, as it is a basic skill in the curriculum. It also addressed the importance of using modern laboratory equipment (the Biosyn system) in detecting the values of linear kinetic variables and their effective impact in training and benefiting from them in developing skills, It also aimed to identify the characteristics of linear kinetics and the extent of their impact on implementing the skill effectively, which makes the process of development or motor learning more effective and positive. Because using these digital values in the training process has many benefits and functions, the most important of which is determining the correct movement paths and other important benefits that work to achieve the greatest possible training and educational efficiency. In addition to saving the effort and time spent on the training unit, the researchers used the descriptive approach and identified the research population, which is the students of the second stage in the College of Physical Education and Sports Sciences, and randomly selected the students of Division C, numbering (30) students. As for the most important conclusions, the results showed the importance of providing information about the series of forces during performance in the main stage and then benefiting from it in interpreting the movement. The results of the linear kinetic curve characteristics of the power series variables showed a consistent shape in the main phase (Striking the ground and flying) with gymnastics for the parts of the body, each according to the amount of its mass and its contribution to the striking stage.